AS THE INVESTIGATOR OF THE ALIENATION OF HUMAN RELATIONS - Edmundas Krakauskas (Problemos)
In Sixties the problem of alienation as my dissertation theme presented by E. Meškauskas not as the ideological problem, but as the sociological one. The alienation of human relations is the real phenomenon not only of the antagonistic class societies (in terms of that days), but also of the socialistic ones. Alienation as a notian must be treated from the cognitive point of view at first. Argumentation must be grounded on the studied facts, not on the ideological or moral evaluations. The most complicated is the question of the future of human relations. It is always in danger of an unrealistic idealization.